Correlation of the aesthetic component of dental health and emotional state in patients with different anxiety levels - O. I. Lobach (Nevrologiâ, Nejropsihiatriâ, Psihosomatika, 2018)
Objective: to investigate the influence of the aesthetic component of dental health on the anxiety level and quality of life of socially active elderly patients. Patients and methods. A total of 32 patients aged 60 to 67 years who had a poor aesthetic appearance of the hard tissues of the front teeth were followed up. All the patients underwent determination of anxiety levels by the Spielberger–Hanin procedure and assessment of quality of life using an abbreviated 26-item version of the World Health Organization Quality of Life (WHOQOL-BREF-26) questionnaire; the updated Oral Health Impact Profile (OHIP-14) was also used. Aesthetic rehabilitation of vital front teeth was carried out using photo composite materials made in Russian and foreign countries. Results. Before treatment, the state anxiety scores were 54±1.4 scores; the trait anxiety ones were 41±1.2 scores; at 1 week after treatment, these were 42±0.5 and 39±0.6, respectively (p ≤ 0.05 for both indicators), and at 6 months, these were 44±0.5 and 43±0.7, respectively. Conclusion. The aesthetic component of dental health in socially active elderly patients is directly proportional to quality of life and inversely proportional to the level of trait or state anxiety. Russian and foreign photo composite restorative materials showed equal sustained performance.